Early changes in system xc− and glutathione in the retina of diabetic rats. (May 2016) - Carpi-Santos, Raul; Ferreira, Marcos Josf; Pereira Netto, Annibal Duarte; Giestal-de-Araujo, Elizabeth; Ventura, Ana Lucia Marques; Cossenza, Marcelo; Calaza, Karin C.
Abstract: Diabetic retinopathy (DR), the main cause of blindness among diabetic patients, affects both neuronal and vascular cells of the retina. Studies show that neuronal cell death begins after 4 weeks of diabetes and could be related with an increase in oxidative stress. System x c − is a glutamate/cystine exchanger, formed by a catalytic subunit called xCT and a regulatory subunit 4F2hc, whose activity is crucial to the synthesis of glutathione, which is a key antioxidant molecule for cells. Although some studies have shown that glutamate transport mediated by excitatory amino acid transporters (EAATs) in diabetic rats is downregulated, there are no studies investigating system x c − in this context. To evaluate whether system x c − is modified by early onset of diabetes, primary retinal cell culture exposed to high glucose and retinas of rats 3 weeks after streptozotocin injection were used. We observed that xCT subunit protein expression both in cultures and in vivo were diminished. Furthermore, system x c − activity and GSH levels were also decreased whereas oxidative stress was increased in retinas of diabetic animals. Therefore, this study raises the possibility that alterations in system x c − expression and activity could occur during early onset of diabetes. In that way, system x c − modifications could be related to increased ROS in diabetic retinopathy. Highlights: Both expression and activity of system x c − is reduced after 3 weeks of diabetes. Glutathione levels are also diminished in the animal model used. Oxidative stress is increased after early onset of diabetes.